2002
DOI: 10.1183/09031936.02.00244602
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast versus fluticasone: effects on lung function, airway responsiveness and inflammation in moderate asthma

Abstract: Whether leukotriene receptor antagonists exhibit adequate antiinflammatory effects in the treatment of asthma is still a controversial issue. The aim of the present study was to perform a direct comparison of the effects of a 4-week treatment with either montelukast (10 mg, once a day) or low-dose inhaled fluticasone (100 mg b.i.d.) on functional and inflammatory parameters in steroid-naïve patients with moderate asthma.Forty patients (forced expiratory volume in one second (FEV1), 60-80% predicted) were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 27 publications
(29 reference statements)
5
26
0
1
Order By: Relevance
“…Not all studies, however, reported on such effects, including an anti-inflammatory action of montelukast [12]. In contrast to the expected 75% protection of the deterioration in PEF under placebo, the actual protection through montelukast was y20% and was nonsignificant.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Not all studies, however, reported on such effects, including an anti-inflammatory action of montelukast [12]. In contrast to the expected 75% protection of the deterioration in PEF under placebo, the actual protection through montelukast was y20% and was nonsignificant.…”
Section: Discussionmentioning
confidence: 73%
“…However, whether clinically introduced antileucotrienes exert significant anti-inflammatory effects is still under discussion. Some studies have shown a reduction in, for example, sputum eosinophils or the level of exhaled NO, whilst others have not [10][11][12]. Irrespective of this, antileucotrienes undisputedly have a bronchodilator and bronchoprotective potential [12,13] and have thus became part of current treatment recommendations in asthma [1].…”
mentioning
confidence: 99%
“…Montelukast has been found to cause a significant decrease in the levels of sputum eosinophil cationic protein [23], soluble interleukin-2 receptor, interleukin-4 and soluble intercellular adhesion molecule-1 and eosinophil blood counts [18]. While studies in adults [20,25,30] and school-aged children [9,31] treated with montelukast have shown a fall in FeNO, the data from the present study illustrate that this effect of montelukast on FeNO is also present in infants and very young children aged ,2 yrs suffering from early childhood asthma. A significant reduction in FeNO after 4 weeks of treatment with montelukast has been shown in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have demonstrated a positive effect on markers of airway inflammation [9,18,20,23,24], namely FeNO and levels of sputum eosinophils and eosinophil cationic protein, others have not [25]. Montelukast is orally administered once daily and is therefore easy to apply.…”
mentioning
confidence: 99%
“…Reporting of sample size calculation Of the 361 search results, 20 studies fulfilled the inclusion criteria [9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. 11 of the 20 (55%) did not report how the sample size was calculated.…”
Section: Resultsmentioning
confidence: 99%